PENGARUH MOTIVASI DAN DIKLAT TERHADAP KINERJA KARYAWAN SWASTA (STUDI KASUS : PT. HASRAT TATA JAYA PEKANBARU) - Aqsa, Muhammad Ali (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This study aims to determine the impact of motivation and education and training on the performance of private employees, in which this research was conducted at PT. Hasrat Tata Jaya Pekanbaru. The number of samples in this study was determined based on Slovin formula, so that a sample of 72 people was obtained, while the approach used in sampling was through simple random sampling. While the data analysis in this study uses quantitative methods with multiple linear regression. Based on the results of research on the motivation variable, the results obtained that the value of t count is greater than t table (2.652> 1.994) with a significance level of 0.010 smaller than 0.05. Then H1 is accepted. Based on the results of the t test above it can be concluded that motivation has a positive and significant effect on the performance of employees at PT. Hasrat Tata Jaya Pekanbaru. While the results of testing on education and training variables, the results obtained that the value of t count is greater than t table (2,084> 1,994) with a significance level of 0.041 smaller than 0.05. Then H2 is accepted, Based on the results of the t test above it can be concluded that education and training has a positive and significant effect on the performance of employees at PT. Hasrat Tata JayaÂ  Pekanbaru. In a simultaneous test (F test), obtained f count greater than f table that is equal to 86,600> 3.13 with a significance level of 0,000 smaller than 0.05, this means that H3 is accepted. Which means that simultaneously the motivation and education variables and training have a positive and significant effect on employee performance variables. So it can be concluded that motivation and education and training together (simultaneous) have a positive and significant effect on the performance of private employees at PT. Hasrat Tata JayaÂ  Pekanbaru. The large impact caused by the two variables is 71.50%, this explains that motivation and education and training have an effect of 71.50% on the performance of employees at PT. The Desire of Tata Jaya Pekanbaru, while the rest was not assessed in this study.